The Role of Budget Management in Maintaining Neighborhood Grocery Store Stability Amid Staple Price Fluctuations - Resky Cahaya Dewi; Wa Ode Rayyani (Jurnal Studi Multidisiplin Ilmu, 2026)
Purpose: This study examines how budget management contributes to maintaining the operational stability of a neighborhood grocery store amid the fluctuating prices of staple goods in Makassar City. Methodology: A descriptive qualitative approach was employed using in-depth interviews, observation, and documentation. Data were analyzed through the Miles, Huberman, and Saldana model, including data condensation, display, and conclusion drawing. Results: Changes in staple goods prices affect procurement costs, working capital, and business profits. The owner responds by managing finances carefully, maintaining simple financial records, and allocating reserve funds to sustain cash flow and business continuity.Conclusions: Budget management applied consistently, even in a simple form, plays an important role in supporting the stability of a neighborhood grocery store, helping the owner control spending, manage working capital, and adapt to staple price changes in the market.Limitations: This study is limited to one informant and focuses only on budget management, so findings cannot represent all neighborhood grocery stores in Makassar City.Contributions: This research offers an empirical picture of budget management practice among micro-enterprises and underscores the importance of financial management in sustaining business resilience amid economic uncertainty.